Enhanced desalination performance of membrane capacitive deionization cells by packing the flow chamber with granular activated carbon. (15th November 2015) - Bian, Yanhong; Yang, Xufei; Liang, Peng; Jiang, Yong; Zhang, Changyong; Huang, Xia
Abstract: A new design of membrane capacitive deionization (MCDI) cell was constructed by packing the cell's flow chamber with granular activated carbon (GAC). The GAC packed-MCDI (GAC-MCDI) delivered higher (1.2–2.5 times) desalination rates than the regular MCDI at all test NaCl concentrations (∼100–1000 mg/L). The greatest performance enhancement by packed GAC was observed when treating saline water with an initial NaCl concentration of 100 mg/L. Several different GAC materials were tested and they all exhibited similar enhancement effects. Comparatively, packing the MCDI's flow chamber with glass beads (GB; non-conductive) and graphite granules (GG; conductive but with lower specific surface area than GAC) resulted in inferior desalination performance. Electrochemical impedance spectroscopy (EIS) analysis showed that the GAC-MCDI had considerably smaller internal resistance than the regular MCDI (∼19.2 ± 1.2 Ω versus ∼1222 ± 15 Ω at 100 mg/L NaCl). The packed GAC also decreased the ionic resistance across the flow chamber (∼1.49 ± 0.05 Ω versus ∼1130 ± 12 Ω at 100 mg/L NaCl). The electric double layer (EDL) formed on the GAC surface was considered to store salt ions during electrosorption, and facilitate the ion transport in the flow chamber because of the higher ion conductivity in the EDLs than in the bulk solution, thereby enhancing the MCDI's desalination rate. Graphical abstract: Highlights: Packing GAC in the MCDI's flow chamber enhanced its desalination performance. The desalination rate of GAC-packed MCDI increased by ∼20–150%. GAC-MCDI is particularly advantageous when treating low salinity water. The EDLs formed on the GAC surface facilitated ion transport in the flow chamber.